Using commensals as proxies for historical inference in the Indian ocean: genetic and zooarchaeological perspectives - Eager, H; Heidi Eager (2014)
The human-abetted introduction of commensal species (i.e. those that opportunistically exploit the anthropogenic environment for food and shelter, e.g. rats, cockroaches etc.) to new areas has occurred throughout history. This has resulted in detrimental ecological changes worldwide but, from a viewpoint of human knowledge, a beneficial corollary of these translocations is that the species in question can be used as proxies to study the movement of the humans who transported them. I reconstruct colonisation histories of three widespread commensal mammalian species in the Western Indian Ocean, the black rat Rattus rattus, house mouse Mus musculus and Asian house shrew Suncus murinus, through phylogeographic studies (the geographic distribution of genetic lineages) of maternally-inherited mitochondrial markers, and zooarchaeological data. The DNA analyses are conducted on samples largely derived from museum specimens collected up to 110 years ago, and from archaeological bones (in the case of rats). I show considerable cryptic diversity in all three species, particularly in mice for which we find a potential major new lineage. Certain lineages within each species predominantly reveal long-distance translocations within the Indian Ocean, but high resolution geographic and genetic clustering is also evident, particularly in Asian house shrews. Phylogeographic structuring of the three species in East Africa and the southern Indian Ocean region (e.g. Madagascar, Reunion, etc.) indicate connections with Arabia, the Middle East, and India in the Islamic period from the first millennium AD, and later European connections during the Age of Exploration. Closer to the origins of the three species (the Indian subcontinent in all cases), range expansions in Eurasia and nearby islands relate to early to mid Holocene human populations, but also with signals of later secondary colonisations. Through ancient DNA studies I found genetic continuity between temporally separated populations of black rats suggesting population persistence, and high levels of diversity in Songo Mnara, a Swahili stonetown in Tanzania. Knowledge of the colonisation history and genetic diversity of an introduced species is essential to understand their resilience in novel landscapes, and to identify pathways of invasion and, by proxy, human trade and exchange networks that facilitated their dispersal. My research contributes significantly to that end for three socially, economically and ecologically important species that are well-established in the Indian Ocean region and beyond.